Misuse of the Concept of Loyalty as a Legitimacy of Wage Rights Violations and Working Time Restrictions: An Analysis of Labor Law Protection in Indonesia - Sepia Walandari; Nadhila safira; Rheny windi Nabila; Mirza Nasution (ISNU Sumatera Utara, 2024)
The development of modern work culture has given birth to the phenomenon of abuse of the concept of loyalty which is often used as legitimacy to justify the provision of work outside the normal working time limit without the fulfillment of the right to overtime wages. This condition creates an imbalance in employment relations and has the potential to ignore the normative rights of workers guaranteed by labor law. This study aims to analyze the legal protection of wage rights and work time restrictions and examine the abuse of the concept of loyalty as a form of legitimacy of violations of workers' rights in labor relations in Indonesia. This study uses a legal research method with a normative juridical approach supported by an empirical juridical approach. Data was obtained through literature studies of laws and regulations, books, scientific journals, and relevant legal documents, then analyzed qualitatively using descriptive-analytical methods. The results of the study show that the provisions regarding working time, overtime, and wages have been comprehensively regulated in laws and regulations, but their implementation has not been fully effective due to the development of a work culture that identifies loyalty with a willingness to work indefinitely and without proper compensation. This practice shifts the meaning of loyalty from ethical values to an instrument of exploitation that is contrary to the principle of labor law protection. This study concludes that loyalty cannot be used as an excuse to reduce or eliminate workers' normative rights. Therefore, it is necessary to strengthen labor supervision and develop a culture of industrial relations that places the protection of workers' rights as an integral part of increasing company productivity.